The Implementation of traditional games based on nature in RA (Raudatul Athfal) in Bangkalan Madura - Adhani, Dwi Nurhayati; Nazarullail, Fikri (Universitas Hamzanwadi, 2020)
This research is located at the Early Childhood Education Unit (Roudlotul Athfal) in Bangkalan Regency by examining traditional games that use natural ingredients. Traditional games are games that use traditional tools and are characteristic of certain regions or have become a distinctive feature in Indonesia. Traditional games use simple tools derived from simple materials and natural materials available in the environment. The purpose of this study was to describe traditional games using natural materials in Bangkalan. Researchers used a qualitative research approach with a type of case study. The data collection methods used by researchers were interviews and observations and the stages of data analysis used an interactive model. The results of this study indicate that the tools used to play traditional games are very dependent on the area where they are played, namely when playing traditional games in coastal areas, the tools used come from the sea such as shells, small corals, tamarind seeds that grow near the beach , and if you play traditional games located near rice fields and plantations, the game tools used use leaves and bamboo trees. Traditional games using natural materials can optimize children's development, such as communication skills, creativity, fine and gross motives.Keywords: traditional games, natural ingredients, child development